ANALYZING TEACHING STRATEGIES FOR ENGLISH READING IN JUNIOR HIGH SCHOOL STUDENTS AMID THE COVID-19 PANDEMIC - Khanafiyah, Rozy; Sofi, Muhammad Jauhari (Journal of Language, Literature and Teaching, 2023)
The COVID-19 pandemic has brought to light numerous challenges in the field of English language learning, including the need for strict adherence to health protocols like school closures, mask mandates, and frequent handwashing. This period required a swift adaptation to blended learning, fostering critical and creative thinking to address COVID-19 issues. This study aims to investigate various strategies utilized by English teachers to enhance reading skills amidst the COVID-19 Pandemic. Transcription data were gathered through observational methods and interviews involving three participants – one teacher and two students. Grounded theory was employed for data analysis, revealing eight strategies for improving students' reading abilities. These strategies include utilizing E-learning (WhatsApp) as a platform for delivering reading materials, employing visual aids like PPT presentations and YouTube videos to illustrate texts, identifying and marking challenging vocabulary in PDF texts, translating sentences using online tools (Google Translate), facilitating oral reading through WhatsApp's voice-notes feature, assigning reading tasks on specific websites or PDFs, engaging in Q and A discussions on WhatsApp, and conducting project discussions via virtual platforms like WhatsApp and Google Meet. This study contributes to the understanding of reading teaching practices for junior high students during the COVID-19 pandemic, thus expanding the knowledge of strategies employed by teachers in the teaching of reading.